Negative thermal expansion material beta-Cu 2-x Zn x V2O7 and methods of making and using the same

CN122977440APending Publication Date: 2026-10-27JIANGSU NOVORAY NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611437884.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0027](1)本发明采用含有多羟基、多羧基、多氨基,或者同时含有羟基、羧基、氨基中两种以上官能团的络合剂,络合剂中的羟基、羧基或者氨基中可以提供富余电子对,与过渡金属的d轨道配位螯合。同时将铜锌盐溶液、钒源溶液按照(铜+锌):钒=1:1摩尔比同时滴加到络合剂溶液中,可以有效保证络合剂按照1:1络合(铜+锌)、钒酸根离子。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977440A_ABST
    Figure CN122977440A_ABST
Patent Text Reader

Abstract

The application discloses a kind of negative thermal expansion materials β-Cu 2‑ x Zn x V2O7 and its preparation method and application. The method uses coprecipitation method, with soluble vanadium source, copper salt, zinc salt as raw material, coprecipitation is carried out in the presence of complexing agent and quaternary ammonium base, then by temperature programmed sintering and annealing, prepared with micron size, high crystallinity and excellent negative thermal expansion characteristics β-Cu 2‑x Zn x V2O7. The preparation method of the application is simple, and the β-Cu 2‑x Zn x V2O7 prepared has a crystallinity of ≥96%, a particle size of ≤2.5 μm, and a linear expansion coefficient of ≤-23.5 ppm / ℃, and is suitable for use as a filler for advanced electronic packaging to improve the thermal expansion properties of the packaging material, thereby reducing the thermal mismatch between the packaging material and components such as chips, solder joints, etc., avoiding structural failure caused by thermal stress, prolonging the service life of the device and reducing maintenance costs, and having a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of negative thermal expansion materials, specifically relating to a negative thermal expansion material β-Cu. 2-x Zn x V2O7, its preparation methods, and applications. Background Technology

[0002] Negative thermal expansion (NTE) materials shrink in size when heated, playing a crucial role in the control of thermal expansion in advanced electronic packaging and precision devices. Zinc-doped copper vanadate (also known as zinc copper vanadate, Cu...) 2-x Zn x V2O7, as a negative thermal expansion material, is an important member of the A2B2O7 family (A and B are +2 and +5 valence metal ions, respectively), and is usually prepared by solid-phase or liquid-phase methods.

[0003] Patent CN119343319A discloses a copper-vanadium composite oxide Cu containing Al atoms in solid solution. x M y V z O t The M element is a metallic element with an atomic number of 11 or higher, excluding copper, vanadium, and aluminum; the aluminum content is 100–30,000 ppm by mass, and the molar number of Al atoms is greater than the molar number of M atoms. The Al, Cu, V, and M sources, added as needed, are mixed under wet or dry conditions; after wet mixing with soluble raw materials, the solvent is removed while maintaining boiling to obtain a mixed raw material; or non-water-soluble raw materials are wet-milled and spray-dried to obtain a raw material mixture; subsequently, one or more high-temperature calcinations are performed to obtain a pure or mixed-phase copper-vanadium composite oxide. However, during the mixing and drying of soluble raw materials, the evaporation of the solvent cannot remove non-structural components. These non-structural components, which balance the charge, remain in the structure, increasing the ionic conductivity of the product and directly causing fatal problems such as leakage, corrosion, electromigration, signal degradation, and damp-heat failure. Simultaneously, boiling solutions cause drastic pH shifts, changes in the state of ions, imbalances in micro-area elemental ratios, and uneven macro-powder composition, resulting in significant elemental deviations within the same batch of samples. Furthermore, for large-volume or high-concentration solutions, boiling easily leads to violent boiling and material spillage, causing material loss. Finally, the calcined product contains stable impurity phases such as vanadium aluminum oxide and alumina, which degrade negative thermal expansion and electrochemical properties.

[0004] Patent CN118786092A discloses a copper-vanadium composite oxide (Cu) containing Li atoms dissolved in it. x M y (V)a P b )O t The M element is a metallic element with an atomic number of 11 or higher, excluding copper and vanadium. Li atoms exist as ions after sintering, increasing the ionic conductivity of the product and directly causing fatal problems such as leakage, corrosion, electromigration, signal degradation, and damp-heat failure. Furthermore, the Li source is lithium metaphosphate, and the introduction of Li also introduces phosphorus. The mixed raw material is obtained by wet mixing of soluble Li, copper, and vanadium sources, followed by removal of the solvent while maintaining boiling. Boiling causes drastic pH shifts, changes in the ionic state, imbalances in micro-area elemental ratios, and uneven macro-powder composition, resulting in significant elemental deviations within the same batch of samples. In addition, for large-volume or high-concentration solutions, boiling easily causes violent boiling and material spillage, leading to material loss.

[0005] Patent CN 121948539 A discloses a method for preparing submicron hollow spherical or near-spherical β-Cu from a water-soluble metal salt mixed solution precursor using ultrasonic atomization and high-temperature calcination. 2-x Zn z V2O7 powder. This method requires the use of nitric acid to adjust the pH to an extremely low range (pH=2~3) during the precursor preparation process, which places high demands on the equipment; and the temperature of the high-temperature calcination stage is higher than 600℃, resulting in relatively high material preparation capacity; in addition, due to the limitations of equipment, the material yield is extremely low, which is not conducive to large-scale production.

[0006] Literature (Negative volume thermal expansion of monoclinic Cu 2-2x Zn 2x A method for preparing zinc-doped copper vanadate pyrovanadate using a solid-state method was proposed in the paper "V2O7 in the temperature range from 93 to 673 K (Journal of Solid State Chemistry, 2020, 285, 121221)". This method uses copper oxide, zinc oxide, and vanadium pentoxide as raw materials, mixes the materials according to stoichiometric ratios, and then sintersects at high temperature to obtain zinc-substituted β-Cu2V2O7. While the solid-state method is suitable for large-scale preparation, the physically ground and mixed raw materials are difficult to achieve uniform dispersion, leading to differences in elemental concentration. Furthermore, the obtained precursor is limited by the particle size of the raw materials; the calcined product particles exhibit significant agglomeration, increasing particle size. This is detrimental to dispersion in advanced electronic packaging and easily leads to stratification when used as a filler, causing differences in the coefficient of thermal expansion. Summary of the Invention

[0007] The purpose of this invention is to provide a negative thermal expansion material β-Cu 2-xZn x V₂O₇, its preparation method, and applications. This method employs a co-precipitation process using soluble vanadium sources, copper salts, and zinc salts as raw materials. Co-precipitation occurs in the presence of a complexing agent and a quaternary ammonium base. Following programmed temperature sintering and annealing, β-Cu with micron-sized particles, high crystallinity, and excellent negative thermal expansion properties is obtained. 2-x Zn x V2O7 can be used as a filler in advanced electronic packaging to improve the thermal expansion properties of packaging materials.

[0008] The technical solution for achieving the objective of this invention is as follows:

[0009] Negative thermal expansion material β-Cu 2-x Zn x V2O7, where x=0.25~0.45, has a crystallinity ≥96%, a particle size ≤2.5μm, and a linear expansion coefficient ≤-23.5 ppm / ℃.

[0010] The aforementioned negative thermal expansion material β-Cu 2-x Zn x The preparation method of V2O7 includes the following steps:

[0011] (1) First, dissolve soluble copper salt and soluble zinc salt in water to form a copper-zinc salt solution. Then, under the conditions of a warm water bath at 40~95℃ and stirring, add the copper-zinc salt solution and the soluble vanadium source solution dropwise to the complexing agent solution at a molar ratio of (copper + zinc):vanadium = 1:1 and a molar ratio of copper:zinc:vanadium = (1.55~1.75): (0.25~0.45):2.0. Stir until the complexation reaction is complete, then add quaternary ammonium base solution to adjust the pH to 8.0~11.5, continue stirring, and then let it stand to precipitate until no obvious precipitate is produced. Take the precipitate and dry it.

[0012] (2) The dried precipitate was subjected to programmed temperature sintering. After sintering, it was washed and dried to obtain the sintered product. The programmed temperature sintering conditions were: heating to 150~200℃ and holding for 90~120 min; then heating to 300~400℃ and holding for 120~150 min; finally heating to 500~600℃ and holding for 240~300 min.

[0013] (3) The sintered product is annealed at a low temperature of 400~500℃ to obtain the negative thermal expansion material β-Cu. 2-x Zn x V2O7.

[0014] Furthermore, in step (1), the soluble copper salts include, but are not limited to, copper sulfate, copper nitrate, copper acetate, copper chloride (CuCl2), copper bromide, copper gluconate, etc.

[0015] Furthermore, in step (1), the soluble zinc salts include, but are not limited to, zinc chloride (ZnCl2), zinc bromide, zinc nitrate, zinc sulfate, zinc acetate, zinc oxalate, zinc gluconate, zinc lactate, etc.

[0016] Furthermore, in step (1), the soluble vanadium source includes, but is not limited to, vanadium chloride (VCl3), vanadium bromide, vanadium oxysulfate (VOSO4), vanadium oxynitrate (VO2NO3), vanadium oxynitrate, vanadium oxynitrate, ammonium metavanadate (NH4VO3), vanadium oxyoxalate pentahydrate (VO(C2O4)·5H2O), etc.

[0017] Furthermore, in step (1), the complexing agent contains multiple hydroxyl, multiple carboxyl, multiple amino groups, or simultaneously contains two or more functional groups of hydroxyl, carboxyl and amino groups, including but not limited to citric acid (C6H8O7), oxalic acid, tartaric acid (C4H6O6), malic acid, ethylenediaminetetraacetic acid, aminotriacetic acid, etc.

[0018] Furthermore, in step (1), when the complexing agent is oxalic acid, a dispersant is also added, which is polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, triethanolamine or glucose.

[0019] Furthermore, in step (1), the quaternary ammonium base includes, but is not limited to, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, methylethylammonium hydroxide, methylpropylammonium hydroxide, tetrabutylammonium hydroxide, etc.

[0020] Further, in step (1), a 20-25 wt.% tetrapropylammonium hydroxide solution is added dropwise to adjust the pH to 7.0-8.0. After stirring for 30-60 minutes, another 20-25 wt.% tetrapropylammonium hydroxide solution is added dropwise to adjust the pH to 8.0-9.0. Stirring continues for 1.5-5 hours.

[0021] Furthermore, in step (1), the stirring time is 2 to 6 hours.

[0022] Further, in step (2), the programmed temperature rise sintering conditions are: rise to 150℃ and hold for 90 min; then rise to 300℃ and hold for 120 min; finally rise to 550℃ and hold for 240 min.

[0023] Furthermore, in step (2), the heating rate is 5~10℃ / min.

[0024] Furthermore, in step (3), the annealing temperature is 450~480℃ and the low-temperature annealing time is 2~3h.

[0025] This invention also provides the above-mentioned negative thermal expansion material β-Cu 2-x Zn xApplication of V2O7 in the preparation of advanced electronic packaging fillers.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] (1) The present invention uses a complexing agent containing multiple hydroxyl, multiple carboxyl, multiple amino groups, or simultaneously containing two or more functional groups of hydroxyl, carboxyl, and amino groups. The hydroxyl, carboxyl, or amino groups in the complexing agent can provide excess electron pairs to coordinate and chelate with the d orbitals of transition metals. At the same time, the copper-zinc salt solution and the vanadium source solution are added dropwise to the complexing agent solution at a molar ratio of (copper + zinc):vanadium = 1:1, which can effectively ensure that the complexing agent complexes (copper + zinc) and vanadate ions in a 1:1 ratio.

[0028] (2) The present invention adopts the co-precipitation method. By controlling the temperature at 40~95℃, the chelation reaction rate is effectively improved. By controlling the pH, the precipitation rate can be regulated to avoid uneven element distribution caused by precursor aggregation due to excessive precipitation. By controlling the stirring speed, the chelation rate of complexing agent with copper and vanadium ions can be regulated, thereby regulating the micro-size of precipitate particles and thus preparing monodisperse micron-sized powder.

[0029] (3) In this invention, quaternary ammonium base is used as a coprecipitant. It can regulate the pH of the solution and promote the precipitation of complexes. It can also be used as a sintering aid in the dried product to improve sintering efficiency and reduce sintering temperature through gas-phase mass transfer.

[0030] (4) The present invention performs low-temperature annealing after programmed temperature sintering, which can effectively improve the crystallinity of powder materials and improve the negative thermal expansion characteristics of materials without changing the powder size.

[0031] (5) The raw materials used in the method of this invention are all water-soluble and suitable for industrial production. The preparation process is simple, and the emissions generated during the preparation process do not contain harmful substances, making it suitable for large-scale production. The β-Cu prepared by this invention... 2- x Zn x V2O7 powder has high crystallinity and high yield, and has excellent negative thermal expansion characteristics and uniform size dispersion. It is suitable as a filler for advanced electronic packaging to improve the thermal expansion properties of packaging materials, thereby reducing thermal mismatch between packaging materials and components such as chips and solder joints, avoiding structural failure caused by thermal stress, extending device life and reducing maintenance costs. It has broad application prospects. Attached Figure Description

[0032] Figure 1 β-Cu prepared in Examples 1 to 8 2-x Zn x XRD pattern of V2O7;

[0033] Figure 2 β-Cu prepared for Comparative Examples 1 to 7 2-x Zn x XRD pattern of V2O7;

[0034] Figure 3 β-Cu prepared in Examples 1-8 and Comparative Examples 1-7 2-x Zn x Scanning electron microscope (SEM) image of V2O7. Detailed Implementation

[0035] The present invention will now be described in further detail with reference to specific embodiments and accompanying drawings.

[0036] Example 1

[0037] β-Cu 1.7 Zn 0.3 The preparation of V2O7 includes the following steps:

[0038] (1) Weigh 28.98 g of copper chloride dihydrate (CuCl2·2H2O, 0.17 mol) and 4.09 g of zinc chloride (0.03 mol) and dissolve them together in 100 mL of deionized water to prepare a copper-zinc salt solution. Weigh 19.212 g of citric acid (C6H8O7, 0.1 mol) and dissolve it in 200 mL of deionized water to prepare a citric acid solution. Weigh 23.40 g of ammonium metavanadate (0.2 mol) and dissolve it in 100 mL of deionized water to prepare an ammonium metavanadate solution.

[0039] (2) Place the citric acid solution in a 50°C water bath and stir at 1000 rpm. Then, simultaneously add the copper-zinc salt solution and ammonium metavanadate solution to the citric acid solution at a rate of 20 mL / min. After the copper-zinc salt solution and ammonium metavanadate solution have been added, maintain the 50°C water bath and continue stirring for 30 min to allow the complexation reaction to proceed fully. Then, add 25 wt% tetrapropylammonium hydroxide to adjust the pH to 7.0-8.0 and continue stirring for 30 min. Continue adding 25 wt% tetrapropylammonium hydroxide to adjust the pH to 8.0-9.0, and reduce the stirring speed to 500 rpm for 30 min, then reduce the stirring speed to 200 rpm for 30 min, then reduce the stirring speed to 50 rpm for 30 min, then stop stirring and let it stand for 2 h to settle. Spread the resulting dark suspension evenly on a PTFE tray and dry it overnight in an 80°C oven.

[0040] (3) The dried product was pulverized and placed in a sintering furnace for programmed temperature sintering. The sintering curve was: room temperature → 150℃, constant temperature for 90 min → 300℃, constant temperature for 120 min → 550℃, constant temperature for 240 min, with a heating rate of 5℃ / min. After sintering, the sintered product was washed twice with deionized water and anhydrous ethanol alternately, and then dried in an oven at 80℃ for 6 h to obtain the sintered product.

[0041] (4) The sintered product was placed in a sintering furnace and heated to 450℃ for constant temperature annealing for 180 min. It was then allowed to cool naturally, with low-temperature air introduced during the cooling process to promote cooling. The cooling rate was 3℃ / min, yielding 33.12g of β-Cu. 1.7 Zn 0.3 The yield of V2O7 powder, calculated based on the molar mass of vanadium, is 97.1%.

[0042] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 97.1%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 1.93 μm.

[0043] Example 2

[0044] The difference between this embodiment and Example 1 is that in step (1), the vanadium source is vanadium oxysulfate pentahydrate (VOSO4·5H2O), and the amount used is 52.62 g (0.2 mol). The other steps are the same as in Example 1. Finally, 32.91 g of β-Cu was obtained. 1.7 Zn 0.3 V2O7 powder, with a yield of 96.5%.

[0045] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 97.2%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 1.92 μm.

[0046] Example 3

[0047] The difference between this embodiment and Example 1 is that in step (1), the vanadium source is vanadium oxalate pentahydrate, with an amount of 68.22 g (0.2 mol), and the vanadium source solution is prepared at 40°C; the maximum sintering temperature in step (3) is 500°C, and the temperature is maintained for 5 hours; the other steps are the same as in Example 1. Finally, 33.44 g of β-Cu was obtained. 1.7 Zn 0.3 V2O7 powder, with a yield of 97.6%.

[0048] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 97.1%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 1.91 μm.

[0049] Example 4

[0050] The difference between this embodiment and Embodiment 1 is that in step (1), the complexing agent is tartaric acid, with a dosage of 36.02 g (0.24 mol), and the complexing agent solution is prepared at 40°C; in step (2), the citric acid solution is placed in a 40°C water bath and stirred, and after the copper-zinc salt solution and ammonium metavanadate solution are added dropwise, the temperature of the water bath is raised to 60°C; the maximum sintering temperature in step (3) is 600°C; the other steps are the same as in Embodiment 1. Finally, 32.80 g of β-Cu was obtained. 1.7 Zn 0.3 V2O7 powder, with a yield of 97.62%.

[0051] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 96.7%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 2.03 μm.

[0052] Example 5

[0053] The difference between this embodiment and Example 1 is that in step (1), the complexing agent is oxalic acid, with a dosage of 21.61 g (0.24 mol), and polyvinyl alcohol (PVA, molecular weight 31000, 0.65 g) is added as a dispersant. The complexing agent solution is prepared at 60°C. In step (3), the maximum sintering temperature is 500°C, and the temperature is maintained for 5 hours. In step (4), the annealing temperature is 480°C, and the temperature is maintained for 3 hours. The other steps are the same as in Example 1. Finally, 32.82 g of β-Cu was obtained. 1.7 Zn 0.3 V2O7 powder, yield 96.1%.

[0054] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 96.9%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 1.97 μm.

[0055] Example 6

[0056] The difference between this embodiment and Example 1 is that in step (1), the copper source is copper nitrate trihydrate (Cu(NO3)2·3H2O), with a dosage of 37.45 g (0.155 mol); the zinc source is zinc nitrate hexahydrate (Zn(NO3)2·6H2O), with a dosage of 13.39 g (0.045 mol); and the vanadium source is vanadium oxynitrate mononitrate, with a dosage of 14.50 g (0.100 mol). The other steps are the same as in Example 1. Finally, 33.07 g of β-Cu was obtained. 1.55 Zn 0.45 V2O7 powder, with a yield of 96.84%.

[0057] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.55 Zn 0.45 The crystallinity of V2O7 powder is 96.8%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 2.06 μm.

[0058] Example 7

[0059] The difference between this embodiment and Example 1 is that in step (1), the amount of copper chloride dihydrate used is 29.83 g (0.175 mol), and the amount of zinc chloride used is 3.41 g (0.025 mol); the other steps are the same as in Example 1. Finally, 32.97 g of β-Cu was obtained. 1.75 Zn 0.25 V2O7 powder, with a yield of 96.6%.

[0060] like Figure 1 As shown, the β-Cu obtained by XRD characterization analysis 1.75 Zn 0.25 The crystallinity of V2O7 powder is 96.8%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 2.04 μm.

[0061] Example 8

[0062] This embodiment is basically the same as Example 1, except that the complexing agent is nitrilotriacetic acid, the amount of which is 58.36 g (0.24 mol), and the temperature of the complexing agent solution is controlled at 80°C; in addition, the pH of the mixture is adjusted to 11.5 with 25 wt.% tetraethylammonium hydroxide. Finally, 33.02 g of β-Cu was obtained. 1.7 Zn 0.3 V2O7 powder, with a yield of 96.7%.

[0063] like Figure 1As shown, XRD characterization analysis revealed that the crystallinity of the β-Cu₂V₂O₇ powder prepared in Example 8 was 96.3%; Figure 3 As shown, SEM characterization revealed that the average particle size was 2.02 μm.

[0064] Comparative Example 1

[0065] Using (Negative volume thermal expansion of monoclinic Cu 2-2x Zn 2x β-Cu was prepared using the method described in the Journal of Solid State Chemistry (2020, 285, 121-221), which describes the preparation of V₂O₇ in the temperature range from 93 to 673 K. 1.7 Zn 0.3 V2O7, the specific steps are as follows:

[0066] S1. According to the molar ratio of copper:zinc:vanadium of 1.7:0.3:1, analytical grade CuO (0.17mol, 13.52 g) powder, zinc oxide powder (ZnO, 0.03mol, 2.44 g), and V2O5 powder (0.1 mol, 18.19 g) were mixed and ground for 2 hours to obtain a mixture.

[0067] S2. A cylinder with a diameter of 10 mm and a height of 10 mm is formed by pressing it under a pressure of 200 MPa using a uniaxial tablet press.

[0068] S3. The sample was placed in a boat and then sintered in a high-temperature tube furnace at a temperature increased to 700 °C at a rate of 5 °C / min for 5 h. It was then allowed to cool naturally to room temperature in air and broken up to obtain 32.83 g of β-Cu. 1.7 Zn 0.3 The yield of V2O7 powder, calculated based on the molar mass of the vanadium source, is 96.1%.

[0069] like Figure 2 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 96.3%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 31.8 μm.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Comparative Example 1 is that in step S1, the amount of CuO powder used is 12.73 g (0.16 mol) and the amount of zinc oxide powder used is 3.26 g (0.04 mol); the remaining steps are the same as in Comparative Example 1. The final yield is 32.86 g of β-Cu. 1.6 Zn 0.4 V2O7 powder, with a yield of 96.2%.

[0072] like Figure 2 As shown, the β-Cu obtained by XRD characterization analysis 1.6 Zn 0.4 The crystallinity of V2O7 powder is 96.2%; for example... Figure 3 As shown, SEM characterization revealed that the average particle size was 32.2 μm.

[0073] Comparative Example 3

[0074] The difference between this comparative example and Example 1 is that in step (2), the copper-zinc salt solution is first added to the citric acid solution at a dropping rate of 10 mL / min. After the copper-zinc salt solution is added, the vanadium oxynitrate solution is then added to the citric acid solution containing the copper-zinc salt at a dropping rate of 10 mL / min. The other steps are the same as in Example 1. The final product is β-Cu containing characteristic peaks of copper oxide, vanadium pentoxide, and zinc pyrovanadate. 1.7 Zn 0.3 V2O7 powder, with a mass of 32.89 g and a yield of 96.3%.

[0075] like Figure 2 As shown, based on the peak area of ​​the β-Cu₂V₂O₇ powder crystals, the β-Cu₂V₂O₇ powder was calculated according to XRD characterization analysis. 1.7 Zn 0.3 V₂O₇ has a crystallinity of 69%, β-Cu 1.7 Zn 0.3 The yield of V₂O₇ was 66.5%; such as Figure 3 As shown, SEM characterization revealed that the average particle size was 2.12 μm.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that in step (3), programmed temperature rise sintering is not used; instead, the temperature is directly raised from room temperature to 550°C and held at that temperature for 240 min at a rate of 5°C / min. All other steps are the same as in Example 1. The final product contains β-Cu with characteristic peaks of zinc pyrovanadate. 1.7 Zn 0.3 V2O7 powder, with a mass of 32.85g and a yield of 96.2%.

[0078] like Figure 2As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The V2O7 powder has a crystallinity of 87%, and β-Cu 1.7 Zn 0.3 The yield of V₂O₇ was 83.7%; such as Figure 3 As shown, SEM characterization revealed that the average particle size was 31.5 μm.

[0079] Comparative Example 5

[0080] The difference between this comparative example and Example 1 is that step (4) is omitted; that is, after high-temperature sintering, the temperature is directly lowered to room temperature without annealing. All other steps are the same as in Example 1. The final product contains β-Cu with characteristic peaks of zinc pyrovanadate. 1.7 Zn 0.3 The mass of V2O7 powder was 32.88 g, and the yield was 96.5%.

[0081] like Figure 2 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The crystallinity of V2O7 powder is 82%; for example Figure 3 As shown, SEM characterization revealed that the average particle size was 30.8 μm.

[0082] Comparative Example 6

[0083] The difference between this comparative example and Example 1 is that the precipitant used in step (2) is a 0.1 mol / L NaOH solution; the highest sintering temperature in step (3) is 715℃, and the other steps are the same as in Example 1. The final product is β-Cu containing characteristic peaks of copper oxide, vanadium pentoxide, and zinc pyrovanadate. 1.7 Zn 0.3 V2O7 powder, with a mass of 33.19 g and a yield of 97.2%.

[0084] like Figure 2 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The V2O7 powder has a crystallinity of 83%, and β-Cu 1.7 Zn 0.3 The yield of V₂O₇ was 80.7%; such as Figure 3 As shown, SEM characterization revealed that the average particle size was 21.4 μm.

[0085] Comparative Example 7

[0086] The literature (Structural characterization and colour of Mg) was used.x Cu 3-x V₂O₈ (0≤x≤3) and Mg y Cu 2-y β-Cu was prepared using the method described in Tena and García-Granda SpringerPlus (2015) 4:163 for the preparation of V2O7 (0≤y≤2) compositions. 1.7 Zn 0.3 V2O7, the specific steps are as follows:

[0087] S1. According to the stoichiometric ratio Cu:Zn:V=1.7:0.3:2.0, accurately weigh 0.03mol ZnCl2 (4.088 g), 0.17mol Cu(NO3)2·2.5H2O (39.541 g) and 0.20 mol NH4VO3 (23.396 g) and dissolve them in 200 mL of deionized water, stirring to form a homogeneous mixed metal salt solution;

[0088] S2. While stirring, add ammonia dropwise to the mixed metal salt solution until the overall pH of the solution is 8, then let it stand to precipitate.

[0089] S3. The obtained precipitate was dried under an infrared lamp and then subjected to programmed temperature sintering. The sintering curves were: 300℃ for 12 h, 600℃ for 12 h, 800℃ for 1 h, and 1000℃ for 1 h. The final product was β-Cu containing characteristic peaks of copper oxide and zinc oxide. 1.7 Zn 0.3 V2O7 powder, with a total mass of 32.56 g and a yield of 95.4%.

[0090] like Figure 2 As shown, the β-Cu obtained by XRD characterization analysis 1.7 Zn 0.3 The V2O7 powder has a crystallinity of 89%, and β-Cu 1.7 Zn 0.3 The yield of V₂O₇ was 84.9%; such as Figure 3 As shown, SEM characterization revealed that the average particle size was 26.4 μm.

[0091] Test Example 1

[0092] 2g of the product powder obtained from Examples 1 to 8 and Comparative Examples 1 to 7 were weighed and compressed into tablets. The tableting conditions were 5MPa and the holding time was 5min. The tablets were compressed into round cakes with a diameter of 10mm. The coefficient of thermal expansion of each sample in the temperature range of 25℃ to 300℃ was determined using a thermomechanical analyzer (TMA Q400). The results are shown in Table 1.

[0093] Table 1. Crystallinity, average particle size, and coefficient of thermal expansion of samples from Examples 1-8 and Comparative Examples 1-7

[0094]

[0095] Based on the XRD characterization results of the samples from Examples 1 to 8 and Comparative Examples 1 to 7 ( Figure 1 , Figure 2 It can be seen that the peak positions of the samples from Examples 1 to 8, Comparative Examples 1, 2, and 5 are consistent with the standard spectrum, which indicates that the samples from Examples 1 to 8, Comparative Examples 1, 2, and 5 are pure β-phase Cu. 2-x Zn x V2O7 material: Low-temperature annealing is beneficial for improving the crystallinity of the material. However, in Comparative Example 5, the precursor was not annealed at low temperature after high-temperature sintering, resulting in a significant broadening of the XRD characteristic peaks of the sintered product and a decrease in crystallinity. The material in Comparative Example 3 was prepared using a liquid-phase complex co-precipitation method. Because copper, zinc, and vanadium were not added simultaneously, a local elemental imbalance occurred, leading to the appearance of impurity or raw material phases after sintering. The material in Comparative Example 4 was prepared using a solid-phase mixed sintering method. The sintering process involved direct heating without low-temperature pre-calcination, resulting in insufficient diffusion and mass transfer between raw materials, competition between copper and zinc, and the appearance of a zinc pyrovanadate phase. The material in Comparative Example 6 was prepared using a liquid-phase complex co-precipitation method. However, NaOH solution was used as the pH adjuster and precipitant during the precipitation process, inducing a faster complex precipitation rate than quaternary ammonium alkali, significantly increasing the particle size. Furthermore, NaOH failed to act as a sintering aid. Therefore, a higher sintering temperature was required to ensure sufficient reaction of the raw materials and obtain the desired product. In Comparative Example 7, the material was prepared by direct liquid-phase precipitation. Ammonia was used as a precipitant during the precipitation process, which induced the precipitation rate to be faster than that of quaternary ammonium base, and the particle size increased. In addition, the two high-temperature stages in the sintering process were 800°C and 1000°C, which were higher than those in other examples and comparative examples, so there was sintering between the particles.

[0096] Figure 1 Examples 1 to 8 and Figure 2The peak intensities of Comparative Examples 1 and 2 differ because the powder pressing method used in XRD powder diffraction sample preparation causes different crystal orientations in the samples. Comparative Example 3 contains multiple impurity phases (Zn₂V₂O₇, CuO, V₂O₅), Comparative Example 4 contains characteristic peaks of zinc pyrovanadate, and Comparative Example 6 uses NaOH as a precipitant, which induces a faster complex precipitation rate than organic bases, resulting in a local imbalance of copper and zinc elements. Therefore, the sintered product contains characteristic peaks of Zn₂V₂O₇, CuO, and V₂O₅. In Comparative Example 7, vanadium exists in oxide form during the sintering precipitation precursor process. When the sintering temperature reaches 800℃ and 1000℃, the free V₂O₅ (melting point ~690℃) volatilizes, leading to an imbalance in the ratio of copper, zinc, and vanadium elements, resulting in characteristic peaks of copper oxide and zinc oxide.

[0097] Examples 1-8 β-Cu 2-x Zn x The yields and crystallinity of the V₂O₇ samples were all above 96%. However, Comparative Examples 1 and 2, prepared using solid-state sintering, produced products with larger particle sizes. The crystallinity of Comparative Example 5 was lower than that of the examples because annealing was not performed during sintering, leading to reduced crystallinity. The sintered product of Comparative Example 3 contained a large number of impurity phases; based on the crystallization peak area in the XRD results, β-Cu... 1.7 Zn 0.3 The V₂O₇ crystallinity was 69%, and the yield was approximately 66.5%. Comparative Example 4, which employed direct heating sintering, produced a product with relatively lower crystallinity compared to the examples, and exhibited characteristic peaks of zinc pyrovanadate. Based on the peak area in the XRD results, β-Cu... 1.7 Zn 0.3 The V₂O₇ crystallinity was 87%, and the yield was 83.7%. Comparative Example 6's sintered product contained a large number of impurity phases. Based on the crystallization peak area in the XRD test results, the β-Cu₂V₂O₇ crystallinity was 83%, and the yield was 80.7%. Comparative Example 7's sintered product, due to excessively high sintering temperature, experienced some vanadium volatilization, resulting in an imbalance in the ratio of copper, zinc, and vanadium, producing impurity phases such as copper and zinc oxides. Based on the crystallization peak area in the XRD test results, the Cu₂V₂O₇ crystallinity was 83%, and the yield was 80.7%. 1.7 Zn 0.3 The crystallinity of V2O7 was 89%, and the yield was 84.9%.

[0098] Depend on Figure 3SEM images of the samples from Examples 1-8 and Comparative Examples 1-7 show that the powder particles of Examples 1-8 and Comparative Examples 2-6 are irregular particles with slightly rough surfaces and relatively smooth edges, while the powder particles of Comparative Example 1 are irregular angular particles. Examples 1-8, Comparative Examples 3, and Comparative Examples 6 are all micron-sized powders prepared by complexation coprecipitation. Comparative Example 6 uses NaOH as a pH adjuster, which induces a faster complexation precipitation rate than the examples, resulting in a significant increase in particle size. In comparison, the alkalinity of NaOH solution is higher than that of ammonia, therefore, the particle size of Comparative Example 6 is larger. Comparative Example 7 uses ammonia as a pH adjuster. After the ammonia solution is added, the metal ions are directly precipitated, resulting in larger particle sizes. Because no complexing agent was introduced into the system, and the sintering temperature was too high, causing the particles to melt together, the particle size is larger than that of Comparative Example 6, and the particle morphology is more angular. Comparative Examples 1, 2, 4, and 5 all used solid-state sintering to prepare β-Cu. 2-x Zn x The V2O7 sample particles exhibited significant agglomeration, resulting in a relatively large average particle size.

[0099] The test results of the coefficient of thermal expansion of the samples of Examples 1 to 8 and Comparative Examples 1 to 7 in Table 1 show that the samples of Examples 1 to 8 all have a coefficient of thermal expansion of less than -23.5 ppm / ℃. The sample of Example 8 has the highest coefficient of thermal expansion, which is mainly because the product of Example 8 has the lowest crystallinity among all examples.

[0100] The samples from Examples 1 to 8 and Comparative Example 3 have similar powder particle sizes, but Comparative Example 3 has an impurity phase, resulting in β-Cu 2-x Zn x The V2O7 content is reduced, and the thermal expansion coefficients of CuO and V2O5 in the impurity phase are positive; therefore, the thermal expansion coefficient of the sample in Comparative Example 3 is higher than that in Examples 1 to 8.

[0101] The samples from Examples 1 to 8, Comparative Examples 1, 2, and 7 all have a crystallinity of over 90%, but the samples from Examples 1 to 8 have a crystallinity of over 95% and smaller powder particle size. Therefore, compared with Comparative Examples 1, 2, and 7, the samples from Examples 1 to 8 have a lower coefficient of thermal expansion.

[0102] In all comparative examples, impurity phases appeared in Comparative Example 3, Comparative Example 4, Comparative Example 6, and Comparative Example 7. The coefficient of thermal expansion of the impurity phase material was higher than that of β-Cu. 2-x Zn x V₂O₇ material, β-Cu 2-x Zn xThe lower the V₂O₇ content, the higher the coefficient of thermal expansion of the prepared sample. Therefore, Comparative Example 3 has the highest coefficient of thermal expansion, while Comparative Example 1 has the lowest. This is mainly because Comparative Example 1 is a pure-phase β-Cu. 1.7 Zn 0.3 V2O7 material has the lowest coefficient of thermal expansion, but because its particle size is much larger than that of the examples, its coefficient of thermal expansion is higher than that of the materials prepared in Examples 1 to 8; Comparative Example 2 sample is pure phase β-Cu. 1.6 Zn 0.4 The V2O7 material has a similar chemical composition to Comparative Example 1, but its particle size is slightly larger, and its coefficient of thermal expansion is slightly higher than that of Comparative Example 1. Comparative Example 5 did not undergo low-temperature annealing during sintering, resulting in a decrease in the crystallinity of the sintered product. Therefore, its coefficient of thermal expansion is higher than that of Examples 1 to 8 and Comparative Examples 1 to 2.

Claims

1. Negative thermal expansion material β-Cu 2-x Zn x V2O7, characterized in that, x=0.25~0.45, with a crystallinity ≥96%, a particle size ≤2.5 μm, and a linear expansion coefficient ≤-23.5 ppm / ℃.

2. The negative thermal expansion material β-Cu as described in claim 1 2-x Zn x The method for preparing V2O7 is characterized by, Includes the following steps: (1) First, dissolve soluble copper salt and soluble zinc salt in water to form a copper-zinc salt solution. Then, under the conditions of a warm water bath at 40~95℃ and stirring, add the copper-zinc salt solution and the soluble vanadium source solution dropwise to the complexing agent solution at a molar ratio of (copper + zinc):vanadium = 1:1 and a molar ratio of copper:zinc:vanadium = (1.55~1.75): (0.25~0.45):2.

0. Stir until the complexation reaction is complete, then add quaternary ammonium base solution to adjust the pH to 8.0~11.5, continue stirring, and then let it stand to precipitate until no obvious precipitate is produced. Take the precipitate and dry it. (2) The dried precipitate is sintered by programmed temperature rise. After sintering, it is washed and dried to obtain the sintered product. The programmed temperature rise sintering conditions are as follows: heat up to 150~200℃ and hold for 90~120 min; then heat up to 300~400℃ and hold for 120~150 min; finally heat up to 500~600℃ and hold for 240~300 min. (3) The sintered product is annealed at a low temperature of 400~500℃ to obtain the negative thermal expansion material β-Cu. 2-x Zn x V2O7.

3. The preparation method according to claim 2, characterized in that, In step (1), the soluble copper salt is copper sulfate, copper nitrate, copper acetate, copper chloride, copper bromide or copper gluconate, the soluble zinc salt is zinc chloride, zinc bromide, zinc nitrate, zinc sulfate, zinc acetate, zinc oxalate, zinc gluconate or zinc lactate, the soluble vanadium source is vanadium chloride, vanadium bromide, vanadium sulfate, vanadium mononitrate, vanadium metanitrate, vanadium trinitrate, ammonium metavanadate or vanadium oxalate pentahydrate, the complexing agent contains multiple hydroxyl, multiple carboxyl, multiple amino groups, or simultaneously contains two or more functional groups of hydroxyl, carboxyl and amino groups, and the quaternary ammonium base is tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, methylethylammonium hydroxide, methylpropylammonium hydroxide or tetrabutylammonium hydroxide.

4. The preparation method according to claim 3, characterized in that, The complexing agents are citric acid, oxalic acid, tartaric acid, malic acid, ethylenediaminetetraacetic acid, or aminotriacetic acid.

5. The preparation method according to claim 4, characterized in that, When the complexing agent is oxalic acid, a dispersant is also added, which may be polyvinyl alcohol, polyethylene glycol, polyvinylpyrrolidone, triethanolamine, or glucose.

6. The preparation method according to claim 2, characterized in that, In step (1), first add a 20-25 wt.% tetrapropylammonium hydroxide solution, adjust the pH to 7.0-8.0, stir for 30-60 min, then add another 20-25 wt.% tetrapropylammonium hydroxide solution, adjust the pH to 8.0-9.0, and continue stirring for 1.5-5 h.

7. The preparation method according to claim 2, characterized in that, In step (1), the stirring time is 2~6h; in step (2), the heating rate is 5~10℃ / min.

8. The preparation method according to claim 2, characterized in that, In step (2), the temperature-controlled sintering conditions are as follows: heat up to 150℃ and hold for 90 min; then heat up to 300℃ and hold for 120 min; finally heat up to 550℃ and hold for 240 min.

9. The preparation method according to claim 2, characterized in that, In step (3), the annealing temperature is 450~480℃ and the low-temperature annealing time is 2~3h.

10. The negative thermal expansion material β-Cu according to claim 1 2-x Zn x Application of V2O7 in the preparation of advanced electronic packaging fillers.

Citation Information

Patent Citations

  • Negative thermal expansion material, manufacturing method thereof and composite material

    CN119343319A

  • Zn-doped hollow spherical Cu2-xZnxV2O7 material and preparation method thereof

    CN121948539A